Hizib Nahdatul Watani Wa Nahdatul Banati Karya TGKH. Zainuddin Abdul Majid (Analisis Gaya Bahasa dan Fungsi Sastra) - Ilham, Budi (Indo-MathEdu Intellectuals Journal, 2023)
Where Hizib Nahdatul Watani Wa Hizib Nahdatul Banati becomes a literary work that has a function and role in the reading community and the author himself who is also a reader of Hizib Nahdatul Watani Wa Hizib Nahdatul Banati. This research is qualitative research, namely research that obtains data and information about the object of research through relevant books and scientific articles and through field observations in the form of interviews with related sources. In this study, two theories were used, namely the first theory in the science of balaghah which was used to express the style of language used in Hizib Nahdatul Watani Wa Hizib Nahdatul Banati. And the second is the theory of literary sociology to reveal the function of literature to the reading society. The result of this research is the book Hizib Nahdatul Watani Wa Hizib Nahdatul Banati in terms of the author's language style using iqtibas, saja', majaz, and ithnab. The function of the book Hizib Nahdatul Watani Wa Hizib Nahdatul Banati for the author is as a prayer, as a defense bull of NWDI and NWBI, as a medium for spreading Nahdlatul Wathan, and as a light for the nation and state. While the function for the Nahdlatul Wathan tariqa group and Nahdlatul Wathan residents is as a bale wall, medicine for disease, savior, and as a medium of allegiance to Allah SWT. In addition, there is also a tradition that has been built, namely the hiziban tradition in the Nahdlatul Wathan community